2021
DOI: 10.1371/journal.pone.0247387
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of protective behavioral strategies and cannabis use motives: An online survey among past-month users

Abstract: Given the constant high prevalence of cannabis use and cannabis dependence, it is important to determine protective behaviors on the individual level, which buffer the effects of risk factors. Protective Behavioral Strategies for Marijuana (PBSM) have been identified to play an important role for harm reduction in adolescent and young adult users. In the present study, we analyzed if PBSM moderate the effects of use motives (captured by the Marijuana Motives Measure, MMM) on the severity of dependence beyond t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…The existing body of literature on cannabis-PBS consistently indicates that using PBS is associated with a reduction in negative cannabis-related consequences and a decrease in cannabis use in terms of frequency and quantity (Bravo et al, 2017;Còté et al, 2022, Genrich et al, 2021Jordan et al, 2022). In alignment with these observations, our regression analyses have demonstrated the predictive validity of both the full-length and short-form S-PBSC concerning cannabis use profile and cannabis-related consequences.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The existing body of literature on cannabis-PBS consistently indicates that using PBS is associated with a reduction in negative cannabis-related consequences and a decrease in cannabis use in terms of frequency and quantity (Bravo et al, 2017;Còté et al, 2022, Genrich et al, 2021Jordan et al, 2022). In alignment with these observations, our regression analyses have demonstrated the predictive validity of both the full-length and short-form S-PBSC concerning cannabis use profile and cannabis-related consequences.…”
Section: Discussionsupporting
confidence: 78%
“…Since its development, many studies (e.g., Bravo, Weinstein, et al, 2019;Richards et al, 2023) have utilized the PBSM (Pedersen et al, 2017), which has been adapted to other languages. Notably, the German version of the 36-item PBSM was recently subjected to psychometric testing in a community online sample (n=362; Genrich et al, 2021), while Coté et al (2022) found support for the unidimensional structure of the French version of the short PBSM-17 in a sample of 211 university students. However, to our knowledge, no studies have examined the psychometric properties of an adapted Spanish version of the PBSM.…”
Section: Scale (S-pbsc)mentioning
confidence: 99%
“…The onset of marijuana use is multi-causal, with multiple motivations for it. As explanatory models for understanding motivations are consolidated (Cooper, 1994;Matalí et al, 2018), knowledge about them will bring benefits from a preventive and psychotherapeutic perspective, ensuring greater success in interventions (Garrison et al, 2021;Genrich et al, 2021;Pons, 2008). Therefore, it is very important to assess motivations, which would not be possible without the availability of instruments adapted to the Peruvian context and that guarantee acceptable psychometric properties to measure this construct (Carretero-Dios & Pérez, 2005;Carretero-Dios & Pérez, 2007;Muñiz et al, 2013;Muñiz et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, an understanding of an individual's reasons for initiating and/or continuing cannabis consumption can help clarify various cannabis related behaviours and risks, which in turn can inform prevention and treatment efforts. For example, past research has found that using cannabis for experimentation was associated with less cannabis use and fewer cannabis related problems, whereas using cannabis for enjoyment, habit, activity enhancement, and altered perception purposes has been associated with increased use and problems ( Lee et al, 2007 ), while using cannabis routinely and as a means to cope was shown to be moderately correlated with severity of use ( Genrich et al, 2021 ). When comparing adults who use cannabis medicinally to those who use it recreationally, Lin et al (2016) found that medicinal users were more likely to have poorer health and more likely to use cannabis daily than those who used recreationally.…”
mentioning
confidence: 99%